The truth about the world : (McGraw-Hill, 2005)
This collection of essays addresses some of the most important issues in philosophy: God, the mind, freedom, knowledge, and ethics. It can accompany James Rachels' new text Problems from Philosophy, or it can stand alone with great effectiveness. The Truth About the World and Problems from Philosophy are at once Rachels' newest contributions to philosophy and his last. In these two books, the respected author found a culminating expression for his love of philosophy